Modelación de erosión hídrica en los cantones de Loja y Olmedo mediante sistemas de información geografíca. - Puglla Puglla, Wilson Xavier (2017)
Soil erosion is a natural process that is accelerated by anthropic activities. The areas susceptible to erosion in the cantons of Loja and Olmedo in the province of Loja were determined through the implementation of the RUSLE model (Revised Universal Soil Loss Equation, using Geographic Information Systems (GIS). Rainfall erosivity (R factor), soil erodability (factor K), slope length and steepness (LS factor), vegetation cover (factor C) and soil conservation practices (factor P). This information allowed to determine the current and potential water erosion. We identified that 73% of the Loja canton (139 061 ha) has an erosion rate less than 10 t ha-1 año-1 (light), while only 1% (996 ha) has a higher erosion rate (>200 t ha-1 año-1, very high). In Olmedo, 59% of the area (6 581 ha) has an erosion rate between 10 - 50 t ha-1 año-1, while 0.1% (10 ha) has a higher erosion rate (>200 t ha-1 año-1, very high). In the sites where erosion was high, the topography and crops without soil conservation practices were the main drivers. We proposed and modeled measures such as reforestation in areas that have been affected by forest fires and crops following the contour lines in agricultural areas, in order to reduce soil erosion rates.